An introduction to the world's oceans - Sverdrup, Keith A (McGraw-Hill Higher Education, 2005)
An introductory book on the history of oceanography. Water and stratigraphic structure on Earth. Seabed and sedimentary properties. physical properties of water. Seawater chemistry. Air structure and movement. Circulation and ocean structure. Currents, waves, tides, shorelines, rivers. Environmental issues and marine life...